Sexual dysfunctions in women with posttraumatic stress disorder following childhood sexual abuse: prevalence rates according to DSM-5 and clinical correlates: original paper - Weiß, Judith; Steil, Regina; Priebe, Kathlen; Lindauer, Petra; Kleindienst, Nikolaus; Fydrich, Thomas; Müller-Engelmann, Meike (Archives of sexual behavior, 2023)
Many women with posttraumatic stress disorder (PTSD) after child sexual abuse (CSA) suffer from sexual problems. However, little is known about the frequency of female sexual dysfunctions (FSD) as defined by DSM-5 among women with PTSD due to CSA. Furthermore, factors related to FSD in this patient population are understudied. To assess prevalence rates and clinical correlates of FSD according to DSM-5 criteria in women with PTSD after CSA, a structured clinical interview for sexual dysfunctions according to DSM-5 criteria was administered in a sample of 137 women with PTSD after CSA. Participants also completed measures for PTSD, depression symptoms, and borderline personality disorder symptoms. The association between FSD, severity of abuse, PTSD-, depression-, borderline symptom severity, and age was examined. In a second step, the association between FSD and PTSD-clusters was assessed. Diagnostic criteria of female sexual interest/arousal disorder (FSIAD) were met by 2.6% of women in our sample. 5.2% met criteria of female orgasmic disorder (FOD), and 11.8% those of genito-pelvic pain/penetration disorder (GPPPD). PTSD symptom severity predicted number of fulfilled criteria of FSIAD and FOD, the cluster “negative alterations in cognition and mood,” was associated with more fulfilled criteria in FSIAD and FOD. The majority of women reported sexual problems, but diagnostic criteria of FSD were met by only a small number of participants. PTSD symptoms, especially the cluster “negative alterations in cognition and mood,” seem to be related to female sexual functioning after CSA.
Online veröffentlicht: 19. Juli 2023
Gesehen am 22.02.2024